(untitled) (Journal of Bio-Science, 2011)
Context: Escherichia coli is shed in the feces of warm blooded animals and humans and thus potential for public health. Detection and characterization of E. coli in the ready-to-eat (RTE) foods concerns due to their presence indicates fecal contamination of the food. Objective: To identify, characterize and RFLP pattern analysis of E. coli isolated from RTE foods vended in Islamic University campus, Kushtia. Materials and Methods: Fifty samples from four types of consumed foods in six student halls of residence, some temporary restaurants of Islamic University, Kushtia were assessed for bacterial contamination by standard methods. Identification and characterization of E. coli isolates were performed using IMViC tests. Genomic DNA was used to perform RFLP pattern analysis. Results: Thirty seven out of 50 (74%) examined samples of RTE foods had E. coli contamination. The highest number of E. coli was isolated from vegetable oriented RTE foods (90.90%) and fish, meat and cereals samples were also significantly E. coli positive. RFLP profiling of two E. coli isolates were observed. Conclusion: The results of this study provide evidence that some RTE foods had unsatisfactory levels of contamination with E. coli. Thus street vended RTE food could be important potential vehicles for food-borne diseases. Molecular characterization may be exploited to identify food borne pathogen among different species. Keywords: Ready-to-eat foods; Escherichia coli; RFLP pattern DOI: http://dx.doi.org/10.3329/jbs.v18i0.8783 JBS 2010; 18(0): 99-103